Effect of the initial orientation on the reaction attributes for Li + FH → Lif + H on an AB initio surface - Ibrahim Ali , Noorbatcha; N., Sathyamurthy (ELSEVIER Science B.V., 1982)
Results of a three-dimensional quasiclassical trajectory investigation of the orientation dependence of the reaction cross section and the product energy distribution are reported for the title reaction on an ab initio potential-energy surface. The reaction is preferred at the F end rather than at the H end of the molecule. Also, the attack by the Li atom at the F end of the molecule leads to a large product rotational excitation while a broadside attack favors a higher vibrational excitation. This is attributed to the collisions occurring at larger impact parameters for the former than for the latter.